Uso de las TIC como herramienta de aprendizaje en tiempos de aislamiento social (2021)
The general objective of this research was to describe the use of ICT as a learning tool in times of social isolation, from the perspective of the Academic Media students of the I.E.D. John F. Kennedy of Aracataca (Magdalena). This study was developed under a descriptive approach, with a non-experimental transectional field design. The sampled population consisted of 60 undergraduate 11 students distributed in morning and night shifts, who answered a questionnaire of 24 easy-to-understand closed questions, the instrument was developed and applied through the Google Forms tool. To evaluate the results of the survey, the data processed by the platform were analyzed, which showed that more than 60% of the sample expressed agreement that its teachers efficiently use ICT as learning tools in times of social isolation, in the same way, there is also 45.5% who say they are moderately agreed that it has been easy to adapt to the learning modality and that they are satisfied with the methodology used by teachers, where the use of WhatsApp, has become an application that has generated a positive impact throughout the educational community.